Multiphysics Modeling of Thorium-Based Fuel Performance With Cr-Coated SiC/SiC Composite Under Normal and Accident Conditions - Liu, Shengyu; Liu, Rong; Qiu, Chengjie; Zhou, Wenzhong (Frontiers in Energy Research, 2021)
Using finite element Multiphysics modeling method, the performance of the thorium-based fuel with Cr-coated SiC/SiC composite cladding under both normal operating and accident conditions were investigated in this work. Firstly, the material properties of SiC/SiC composite and chromium were reviewed. Then, the implemented model was simulated and the results were compared with that of FRAPTRAN code to verify the correctness of the model used in this work. Finally, the fuel performance of the Th0.923U0.077O2 fuel, Th0.923Pu0.077O2 fuel and UO2 fuel combined with the Cr-coated SiC/SiC composite cladding and Zircaloy cladding respectively were investigated and compared under both normal operating and accident conditions. Compared with the UO2 fuel, the Th0.923U0.077O2 and Th0.923Pu0.077O2 fuels were found to increase the fuel centerline temperature under both normal operating and Reactivity Initiated Accident (RIA) conditions but decrease the fuel centerline temperature under Loss Of Coolant Accident (LOCA) condition. Moreover, compared to the UO2 fuel with the Zircaloy cladding, thorium-based fuels with Cr-coated SiC/SiC composite cladding were found to give better mechanical performance such as delaying the failure time by about 3s of the Cr-coated SiC/SiC composite cladding under LOCA condition, and reducing the plenum pressure by about 0.4 MPa at the peak value in the fuel rod and the hoop strain of the cladding by about 16% under RIA condition.